2021
DOI: 10.1371/journal.pone.0261951
|View full text |Cite
|
Sign up to set email alerts
|

Post-cesarean section surgical site infection and associated factors in East Gojjam zone primary hospitals, Amhara region, North West Ethiopia, 2020

Abstract: Purpose Maternal surgical site infection after cesarean delivery is a clinical problem which contributes to significant morbidity and mortality. In Ethiopia admissions following cesarean section due to surgical site infection have been routine activities of health care institutions but there is limited scientific evidence on both the magnitude of the problem and factors associated with it making prevention mechanisms less effective. Therefore, this study aimed to assess magnitude and risk factors of post-cesar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
1
9
1
Order By: Relevance
“…A literature scan indicated that a previous study done in Egypt reported the association of parity with SSIs [24]. The results of this study are contradictory to the outcome of a couple of studies done in other cities of Ethiopia, which reported that parity is not associated with SSIs [14,37].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A literature scan indicated that a previous study done in Egypt reported the association of parity with SSIs [24]. The results of this study are contradictory to the outcome of a couple of studies done in other cities of Ethiopia, which reported that parity is not associated with SSIs [14,37].…”
Section: Discussioncontrasting
confidence: 99%
“…A scan of the literature indicated that in Ethiopia, only limited data exist which describe the epidemiology of PSWI, the causative organisms, or the incidence of antimicrobial drug resistance, and often, there is no information linked to the post-discharge surveillance programs. Furthermore, risk factors linked to PSWI, too, showed wider variations in several Ethiopian studies [13][14][15][16][17]. In addition, the incidence of infections may vary, depending on the surgeon, hospital, surgical procedures applied, and patient.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, SSIs contribute to mortality and morbidity among patients following surgeries, whereby, globally, one-third of operated patients' deaths are SSIs-related [14]. SSIs following caesarian section (CS) remain one of the signi cant threats to public health with an imperative exerted impacts on human and economic resources, health facilities, and patients as well as antibiotic resistance and, thus compromising the global surgery success [11][12][13].…”
mentioning
confidence: 99%
“…Even though World Health Organization (WHO) recommends an optimal CS rate of 5 to 15%, this rate has been increasing in both developed and developing countries, with an increasing worldwide rate ranging from 6 to 27.2% [13,20], and its signi cant decrease has yet to be anticipated by experts in two decades [9,21]. Nonetheless, the delivery by CS increases up to 20 times the likelihood of developing infections than spontaneous delivery [22,23].…”
mentioning
confidence: 99%
See 1 more Smart Citation